Reading today “Letter to a Professor” (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The article reports the unpublished report held by Professor Riccardo Massa in 1989 as part of a conference entitled "Don Milani and teacher training. Massa wondered about the relevance of Don Milani's thought and how "Letter to a Professor" is placed in the pedagogy of contestation in relation to both the Marxist and Catholic strands. The text is introduced by a rich note by Professor of Pedagogy Jole Orsenigo.
Keywords: don Milani; Letter to a Professor; pedagogy; contestation